Probability and Heisenberg Uncertainty of He+ at Quantum Numbers n≤3 - Supriadi, Bambang; Afidah, Zidan; Arsita, Maya; Ni’mah, Simatun; Hermansyah, Moh Dimas Feri; Wardhany, Merry Khanza Kusuma (Universitas Ahmad Dahlan, 2024)
The purpose of this study is to analyze the probability and uncertainty of electron linear momentum in with the Heisenberg uncertainty approach. Measurement of the position and momentum of atomic electrons is probabilistic. The probability and uncertainty of electron linear momentum are analysed analytically, and simulations of hydrogenic atoms' normalized radial wave function are performed. they can be viewed as hydrogenic atoms with only one electron orbital. The probability and uncertainty of electron linear momentum in decrease with increasing values of the principal quantum number n ≤ 3. While the uncertainty of the electron position is increasing. The results of this study are in accordance with the characteristics of position and linear momentum that are not commutable. The increase in the value of the main quantum number means that the electron's position against this is getting farther, and the speed in the orbital is getting smaller.